Romila Thapar, Sakuntala: Texts, Reading, Histories - Sengupta, Saswati (Religions of South Asia, 2013)
Romila Thapar, Sakuntala: Texts, Reading, Histories. New York: Columbia University Press, 2011. xii + 271 pp. $29. ISBN: 978-0-231-15655-4 (paperback).